Recombinant chymase inhibits fibrinolysis induced by endogenous plasmin in clotted human blood - Vincent, Laurence; Lapointe, Catherine; McDonald, Patrick P.; Rammos, Christos; Rassaf, Tienush; Köllnberger, Maria; Tinel, Hanna; Heitmeier, Stefan; D’Orléans-Juste, Pedro (Frontiers in Immunology, 2025)
BackgroundOur group recently reported that chymase, a serine protease synthetized and released by mast cells, plays a pivotal role in thrombi stabilization in murine deep vein thrombosis (DVT) models, by interfering with the fibrinolytic properties of endogenous plasmin within thrombi. However, the impact of mast cell-derived chymase on endogenous plasmin activity in human blood clots has yet to be explored.MethodsThe antifibrinolytic properties of human recombinant chymase (rCMA-1) were investigated using an in vitro thrombolysis assay based on halo-shaped human blood clots. In addition, a fluorogenic assay was used to detect chymase activity in human thromboembolic biopsies. In both assays, the activity of human chymase was validated using a specific chymase inhibitor, fulacimstat (BAY 1142524).ResultsAlthough rapidly neutralized in plasma, rCMA-1 remains active within the local microenvironment of a blood clot, inducing resistance to endogenous plasmin-mediated fibrinolysis in the presence of recombinant tissue plasminogen activator (tPA). This leads to a concentration-dependent decrease in clot lysis by rCMA-1. The plasmin-inactivating properties of rCMA-1 were inhibited by fulacimstat, resulting in an accelerated clot dissolution. The pro-fibrinolytic effects of fulacimstat in human blood clots were reversed by a plasminogen/plasmin inhibitor, BAY 1214237. Finally, fulacimstat-sensitive chymase activity was identified in thrombi collected from thrombectomy patients, supporting the potential role of the mast cell-derived serine protease in human blood clot stabilization under pathological conditions.ConclusionThese in vitro experiments with human whole blood suggest that mast cell-derived chymase impairs blood clot resolution by interfering with the fibrinolytic activity of endogenous intra-clot plasmin. Our findings provide evidence that recombinant mast cell chymase interferes with endogenous plasmin activity in human whole blood clots in vitro and support the potential of chymase inhibitors, such as fulacimstat, as fibrinolytic agents for thrombotic and thromboembolic disorders.